Building a SEM Analytics Reporting Portfolio. Issue 1 (April 2016) - Goff, Jay W.; Williams, Brian G.; Kilgore, Wendy
Abstract : Effective strategic enrollment management (SEM) efforts require vast amounts of internal and external data to ensure that meaningful reporting and analysis systems can assist managers in decision making. A wide range of information is integral for leading effective and efficient student recruitment and retention programs. This article is designed to help college and university enrollment professionals initiate a SEM analytics reporting portfolio that focuses on shifting the attention of reporting systems from transactional data gathering to shared performance understandings that can be leveraged throughout the enterprise on a timely basis. By employing a K–20 student pipeline planning approach, the authors discuss reporting fundamentals for enrollment management data analytics, the components of a comprehensive reporting portfolio, strategies for building SEM‐focused research organizations, and data interpretation methods.